2021
DOI: 10.3389/fonc.2021.683869
|View full text |Cite
|
Sign up to set email alerts
|

MRCP Combined With CT Promotes the Differentiation of Benign and Malignant Distal Bile Duct Strictures

Abstract: ObjectiveTo determine whether contrast-enhanced computed tomography (CT) can promote the identification of malignant and benign distal biliary strictures (DBSs) compared to the use of magnetic resonance cholangiopancreatography (MRCP) alone and to identify imaging findings of malignant DBSs.Materials and MethodsA total of 168 consecutive patients with confirmed DBSs were reviewed. MRCP alone and MRCP combined with CT images were blindly analyzed by two radiologists (e.g., stricture pattern, margins), and malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As time progresses, the enhancement of fibrotic tissue becomes more pronounced [ 105 , 106 ]. In comparison with benign strictures, extrahepatic bile duct cancer exhibits a thicker bile duct wall, a longer extent of the involved duct, and an irregular lumen [ 107 - 110 ]. When these imaging characteristics were combined in retrospective studies, they identified malignant strictures with an accuracy of 100% and benign strictures with an accuracy of 87% [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As time progresses, the enhancement of fibrotic tissue becomes more pronounced [ 105 , 106 ]. In comparison with benign strictures, extrahepatic bile duct cancer exhibits a thicker bile duct wall, a longer extent of the involved duct, and an irregular lumen [ 107 - 110 ]. When these imaging characteristics were combined in retrospective studies, they identified malignant strictures with an accuracy of 100% and benign strictures with an accuracy of 87% [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with benign strictures, extrahepatic bile duct cancer exhibits a thicker bile duct wall, a longer extent of the involved duct, and an irregular lumen [ 107 - 110 ]. When these imaging characteristics were combined in retrospective studies, they identified malignant strictures with an accuracy of 100% and benign strictures with an accuracy of 87% [ 109 ]. However, various benign inflammatory conditions such as postinflammatory fibrotic strictures, primary sclerosing cholangitis, immunoglobulin G4-related sclerosing cholangitis, recurrent suppurative cholangitis, and ischemic cholangitis can also mimic similar imaging findings.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed the published literature to assess the MRCP criteria of differentiating malignant from biliary strictures. As pe Nirhale et al, (1) , Shabanikia et al ., (19) , Wang et al ., (20) , Suthar . et al, (21) irregular, long, asymmetric, or abrupt narrowing of the biliary and/or pancreatic duct were considered as malignant features.…”
Section: Our Findings Keep With What Was Mentioned Bymentioning
confidence: 99%
“…There are many reasons for mechanical BS, such as malignant tumors, biliary stones, in ammation, and postoperative anastomotic stenosis. In the past few decades, great progress has been made in BS imaging, such as intraluminal ultrasound, MRCP and enhanced CT scanning [4][5] . These noninvasive imaging systems can quickly obtain the relevant BS anatomical information, but how to complete pathological biopsy of the narrow BS is the most critical information for the nal diagnosis.…”
Section: Introductionmentioning
confidence: 99%